2012
DOI: 10.4041/kjod.2012.42.2.56
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional soft tissue analysis for the evaluation of facial asymmetry in normal occlusion individuals

Abstract: ObjectiveTo identify the right and left difference of the facial soft tissue landmarks three-dimensionally from the subjects of normal occlusion individuals.Materials and MethodsCone-beam computed tomography (CT) scans were obtained in 48 normal occlusion adults (24 men, 24 women), and reconstructed into 3-dimensional (3D) models by using a 3D image soft ware. 3D position of 27 soft tissue landmarks, 9 midline and 9 pairs of bilateral landmarks, were identified in 3D coordination system, and their right and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 12 publications
3
30
0
2
Order By: Relevance
“…The current results agreed with other studies (2,4,28,29) . This finding also was confirmed by Hwang et al (30) , who demonstrated that the degree of facial asymmetry tended to increase with the lower and lateral positioning of landmarks. However, the present study disagreed with the study carried by Frakas and Cheung (31) , who found that the most asymmetric part of the face (69.2%) was the upper third .…”
Section: Discussionsupporting
confidence: 74%
“…The current results agreed with other studies (2,4,28,29) . This finding also was confirmed by Hwang et al (30) , who demonstrated that the degree of facial asymmetry tended to increase with the lower and lateral positioning of landmarks. However, the present study disagreed with the study carried by Frakas and Cheung (31) , who found that the most asymmetric part of the face (69.2%) was the upper third .…”
Section: Discussionsupporting
confidence: 74%
“…43 Because of aging, which results in a decrease in soft tissue strength, the soft tissue change one year after surgery would have mixed effects. 6,44 We added the patient age and gender as predictor variables, which is one of the default design settings in biostatistics.…”
Section: Suh Et Al Predicting Soft Tissue Changes After Mandibular Smentioning
confidence: 99%
“…Several researchers have developed standard values for the normal range of asymmetry by obtaining bilateral differences of landmarks in rectangular coordinates for hard or soft tissue analysis on 3D CT 21,22,25,26. However, there has been no study on the normal range of asymmetry of facial lines.…”
Section: Discussionmentioning
confidence: 99%